The use of the DTO™ hybrid dynamic device: a clinical outcome- and radiological-based prospective clinical trial - Christian Herren; Rolf Sobottke; Miguel Pishnamaz; Max Joseph Scheyerer; Jan Bredow; Leonard Westermann; Eva Maria Berger; Stavros Oikonomidis; Peer Eysel; Jan Siewe (BMC Musculoskeletal Disorders, 2018)
Abstract Background The purpose of this study was to assess the radiological and clinical outcome parameters following lumbar hybrid dynamic instrumentation with the focus on the adjacent segment degeneration (ASD) and adjacent segment disease (ASDi). Methods In this prospective trial all patients presenting with degenerative changes to the lumbar spine have been included. Precondition was a stable adjacent level with/without degenerative alteration. The elected patients underwent a standardised fusion procedure with hybrid instrumentation (DTO™, Zimmer Spine Inc., Denver, USA). Patients’ demographics have been documented and the follow-up visits were conducted after 6 weeks, and then stepwise after 6 up to 48 months. Each follow-up visit included assessment of quality of life and pain using specific questionnaires (COMI, SF-36, ODI) and the radiological evaluation with focus on the adjacent level alterations. Results At a mean follow up of 24 months an incidence of ASD with 10.91% and for ASDi with 18.18% has been observed. In 9% a conversion to standardised fusion was needed. There was a high rate of mechanical complication: (1) screw loosening (52.73%), (2) pedicle screw breakage (10.91%), and (3) rod breakage (3.64%) after a follow up of a maximum of 60 months. There were no significant difference of COMI, ODI and SF-36(v2) in comparison to all groups but all 55 patients showed a clinical improvement over the time. Conclusion The dynamic hybrid DTO™ device is comparable to the long-term results after standardised fusion procedure, while a high rate of mechanical complication decreased the initial benefit. Trial registration This trial was registered at the ClinicalTrials Register (#NCT03404232, 2018/01/18, registered retrospectively).